Geomorphologic Phenomenon of Marly Hills and its Effect on Chemical Quality of the Agricultural Water (case study: Kalateh-Sadat watershed of Sabzevar) - Leila Montaseri; Abolghasem Amir Ahmadi; Mohammad Ali Zangeneh Asadi (تحقیقات کاربردی علوم جغرافیایی)
Abstract